2016
DOI: 10.1177/2325967116648441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indiana High School Football Injury Rates by Inclusion of the USA Football “Heads Up Football” Player Safety Coach

Abstract: Background:In Indiana, high school football coaches are required to complete a coaching education course with material related to concussion awareness, equipment fitting, heat emergency preparedness, and proper technique. Some high schools have also opted to implement a player safety coach (PSC). The PSC, an integral component of USA Football’s Heads Up Football (HUF) program, is a coach whose primary responsibility is to ensure that other coaches are implementing proper tackling and blocking techniques alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 15 publications
1
70
0
Order By: Relevance
“…Kerr et al 64 examined the combined effectiveness of a Heads Up First Education Program and limiting contact in practices in youth football and found no protective effect in reducing concussion risk combined or individually in games or practices. However, in a later study, Kerr et al 63 demonstrate a protective effect of introducing a player safety coach in reducing the risk of concussion in practices. Tackle training without helmets and shoulder pads in youth football did not lead to a reduction in head impacts in games 65.…”
Section: Resultsmentioning
confidence: 94%
“…Kerr et al 64 examined the combined effectiveness of a Heads Up First Education Program and limiting contact in practices in youth football and found no protective effect in reducing concussion risk combined or individually in games or practices. However, in a later study, Kerr et al 63 demonstrate a protective effect of introducing a player safety coach in reducing the risk of concussion in practices. Tackle training without helmets and shoulder pads in youth football did not lead to a reduction in head impacts in games 65.…”
Section: Resultsmentioning
confidence: 94%
“…Nine out of 13 studies had a low risk of bias due to missing outcome data; most studies included data for all participants. Three studies provided no information regarding missing data and were therefore rated as no information for this category [7,9,14]. Six studies were rated as having a serious risk of bias in measurement outcomes; these studies had only one group and the outcome measures could be influenced by the knowledge of the intervention [4,8,10,11,15,16].…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Two studies used randomized designs to examine the influence of the HUF program coach education on the incidence of concussion in youth athletes [7,9]. Kerr et al (2015) [9] (N = 70) found that players whose coaches who completed the HUF education program experienced 24% fewer head-impacts above 10Gs, compared to those whose coaches received no educational training.…”
Section: Usa Football's Heads Up Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the education of parents, coaches, physicians, and players about the benefits of early diversification and the harms of early specialization, including stress, injury, and burnout, is crucial. Training programs for coaches regarding the safety of players have proven effective in this regard (Kerr et al, 2016). Similarly, misperceptions related to the likelihood of youth becoming elite athletes ought to be corrected, and the links between parental pressure and child disengagement should be publicized.…”
Section: B What Can Be Done?mentioning
confidence: 99%